Protocol for the development of a core outcome set for stillbirth care research (iCHOOSE Study). Issue 2 (9th February 2022) - Bakhbakhi, Danya; Fraser, Abigail; Siasakos, Dimitris; Hinton, Lisa; Davies, Anna; Merriel, Abi; Duffy, James M N; Redshaw, Maggie; Lynch, Mary; Timlin, Laura; Flenady, Vicki; Heazell, Alexander Edward; et al.
Abstract : Introduction: Stillbirth is associated with significant physical, psychosocial and economic consequences for parents, families, wider society and the healthcare system. There is emerging momentum to design and evaluate interventions for care after stillbirth and in subsequent pregnancies. However, there is insufficient evidence to inform clinical practice compounded by inconsistent outcome reporting in research studies. To address this paucity of evidence, we plan to develop a core outcome set for stillbirth care research, through an international consensus process with key stakeholders including parents, healthcare professionals and researchers. Methods and analysis: The development of this core outcome set will be divided into five distinct phases: (1) Identifying potential outcomes from a mixed-methods systematic review and analysis of interviews with parents who have experienced stillbirth; (2) Creating a comprehensive outcome long-list and piloting of a Delphi questionnaire using think-aloud interviews; (3) Choosing the most important outcomes by conducting an international two-round Delphi survey including high-income, middle-income and low-income countries; (4) Deciding the core outcome set by consensus meetings with key stakeholders and (5) Dissemination and promotion of the core outcome set. A parent and public involvement panel and international steering committee has been convened to coproduce every stage of the development of this core outcome set. Ethics and dissemination: Ethical approval for the qualitative interviews has been approved by Berkshire Ethics Committee REC Reference 12/SC/0495. Ethical approval for the think-aloud interviews, Delphi survey and consensus meetings has been awarded from the University of Bristol Faculty of Health Sciences Research Ethics Committee (Reference number: 116535). The dissemination strategy is being developed with the parent and public involvement panel and steering committee. Results will be published in peer-reviewed specialty journals, shared at national and international conferences and promoted through parent organisations and charities. PROSPERO registration number: CRD42018087748.